Developing junior high school students’ worksheet to foster mathematics communication ability - Cahdriyana, Rima Aksen; Hariyanto, Naufal Yan (International Journal on Education Insight, 2022)
This study aims to develop student worksheets based on mathematical communication skills. It used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop and evaluate the worksheet. The subjects of this study were students of class VII in one of the junior high schools in Yogyakarta. The testing consisted of two stages, namely the small-scale trial consisting of 5 students and a large-scale trial consisting of 31 students. We collected the data using questionnaire for material and media experts’ judgment as well as for the students’ responses. Then, we analyzed the validity and practicality of the worksheet. Finally, the results of the assessment of material experts and media experts obtained an overall average score of 4.29 (very good category), so that the mathematical communication skills worksheet considered valid. Meanwhile, the students' responses to the worksheets were practical with an average score of 3.1 (good category).